ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN BURUH NELAYAN DI PANTAI SENDANGBIRU DESA TAMBAKREJO KABUPATEN MALANG - Daniel Agustinus Aryanto; Sudarti Sudarti (Program Studi Ekonomi Pembangunan, 2017)
The aim of this research was to find out factor effect of work experience, working hours and mileage toward income of fishermen in Sendangbiru beach, Tambakrejo village, Malang District. Tool analysis used Multiple Linear Regression and used statistic test and Classic assumption test. The result of the research showed variables of work experience, working hours and mileage increased, so the income of fishermen also increased. Keywords: Fishermen, work experience, working hours, and mileage.